Survey on whiteflies and their parasitoids in cassava mosaic pandemic areas of Tanzania using morphological and molecular techniques - Guastella, D.; Lulah, H.; Tajebe, L.; Cavalieri, V.; Evans, G.; Pedata, P.A.; Rapisarda, Carmelo; Legg, James P. (Wiley, 2015)
Bemisia tabaci (Gennadius) is the vector of cassava mosaic geminiviruses (CMGs) and cassava brown streak viruses (CBSVs) in Africa, which cause devastating yield losses. As a prerequisite to developing biological control methods and enhancing knowledge of the fauna of whitefly parasitoids in sub-Saharan Africa, endemic parasitoids were surveyed in the cassava-growing regions of Tanzania and analysed using both morphological and molecular methods. An attempt was made to corroborate the identification of the parasitoid species on the basis of consideration of their morphology and sequence analyses of three DNA fragments, namely partial cytochrome oxidase I (COI), the D2 expansion segment of the 28S rRNA and the internal transcribed spacer I (ITS1).